Antioxidant activities of novel resveratrol analogs in breast cancer. Issue 1 (28th September 2017) - Chatterjee, Anwesha; Ronghe, Amruta; Padhye, Subhash B.; Spade, David A.; Bhat, Nimee K.; Bhat, Hari K.
Abstract: The objective of the present study was to characterize the role of novel resveratrol (Res) analogs: 4‐(E)‐{(4‐hydroxyphenylimino)‐methylbenzene, 1, 2‐diol} (HPIMBD) and 4‐(E)‐{(p‐tolylimino)‐methylbenzene‐1, 2‐diol} (TIMBD) as potent antioxidants against breast cancer. Non‐neoplastic breast epithelial cell lines MCF‐10A and MCF‐10F were treated with 17β‐estradiol (E2), Res, HPIMBD, and TIMBD for up to 72 h. mRNA and protein levels of antioxidant genes, superoxide dismutase 3 (SOD3) and N‐quinoneoxidoreductase‐1 (NQO1) and transcription factors, nuclear factor erythroid 2‐related factor (Nrf) 1, 2 and 3 were quantified after the above treatments. Generation of reactive oxygen species (ROS) was measured by CM‐H2‐DCFDA and oxidative‐DNA damage was determined by measuring 8‐hydroxy‐2‐deoxyguanosine (8‐OHdG). HPIMBD and TIMBD scavenged cellular ROS production, attenuated oxidative DNA damage, increased mRNA and protein expression levels of SOD3 and NQO1 and activated Nrf signaling pathway. Our studies demonstrate that HPIMBD and TIMBD have the potential as novel antioxidants to prevent development of breast cancer.